A Web-Based Mindful Parenting Program to Strengthen Parental Competence - Arri Handayani; Padmi Dhyah Yulianti; Ika Menarianti (Universitas PGRI Yogyakarta, 2026)
The intricacy of modern parenting dilemmas necessitates innovative solutions that cater to parents' requirements. Incorporating the principle of mindful parenting into a digital medium provides a means to improve parenting proficiency. This study sought to develop and assess the validity, feasibility, and efficacy of a web-based Mindful Parenting program intended to enhance parenting competence. This research and development approach used the ADDIE model, producing a web-based mindful parenting program. The participants consisted of 112 parents and expert judges in media, language, and family psychology. Experts said Web-Based Mindful Parenting was feasible with content enrichment and accessibility suggestions. The study measured mindful parenting practices using the IM-P scale (31 items, α = .953). A summative evaluation using a one-group pretest–posttest design and the Wilcoxon Signed-Rank Test yielded Z = −8.32, p < 0.001, with a Cohen’s d value of 0.83, indicating that the intervention effectively improved mindful parenting practices. These findings contribute to the literature by integrating the concept of mindful parenting into a digital platform designed to accommodate parents’ needs across stages of family development. Practically, the program enables parents to acquire parenting skills without face-to-face interaction. The program provides psychologists and counselors with a framework for incorporating online services into their professional practice. Future research may add support services and programs to meet the complexity of parenting needs. Keywords: mindful parenting, parenting competence, web-based intervention, web-based mindfulness parenting program